Analisis Produktivitas Tenaga Kerja dan Pendapatan Usaha Home Industry Anugrah Bakery di Bone Bolango - Tesa Amelia Putri Ibrahim; Supriyo Imran; Mohammad Zubair Hippy (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2025)
This study aims to analyze (1) the labor productivity of Anugrah Bakery home industry in the bread production process, (2) the factors influencing labor productivity in the Anugrah Bakery home industry, and (3) the income generated by Anugrah Bakery home industry. This research was conducted from June to July 2024 by involving six active workers as respondents. The variables analyzed include productivity, labor, production costs, and business income. Data obtained through primary and secondary data sources, with data collection methods using observation, interviews, and literature studies. The analytical tools used include productivity analysis to see work productivity in the last 5 years, cost and revenue analysis to identify the effect of costs and labor on business income, and qualitative-quantitative descriptive analysis to provide an overview of factors affecting labor productivity. This study employed both primary and secondary data sources, utilizing qualitative and quantitative data. Data were collected through observation, interview, and literature review. The findings show that (1) labor productivity has been unstable over the past five years. In 2020, productivity reached 54,000 units, but it declined to 37,266 units in 2021 and further decreased to 32,787 units in 2022. (2) Labor productivity in Anugrah Bakery is influenced by internal factors such as the type of raw materials, equipment efficiency, the application of technology and innovation, and the working environment. External factors, including fluctuations in demand and market competition, also impose pressures that influence efficiency and worker motivation. Additionally, (3) the income of Anugrah Bakery has decreased over the past five years. The highest income was recorded in 2022 at IDR 180,009,664, while the lowest was in 2024 at IDR 119,370,000.